Polymer matrix-natural fiber composites: An overview. Issue 1 (1st January 2018) - Yashas Gowda, T.G.; Sanjay, M.R.; Subrahmanya Bhat, K.; Madhu, P.; Senthamaraikannan, P.; Yogesha, B.
Abstract: The study of polymer matrix composites had become an important topic for academic and industrial research. The current thrust for materials which are environmental friendly and biodegradable made researchers to focus on alternate options to synthetic materials. One major area of research in this direction is in the area composites of polymers with natural fibers. These composites exhibit moderate to good mechanical properties. This overview briefs about the use of polymers for different natural fiber composites. This review is expected to provide a general overview for the materials selection for the design of composite materials with improved properties.